Administering the Value-Added Tax on Imported Digital Services and Low-Value Imported Goods - Brondolo, John (Technical Notes and Manuals; Technical Notes and Manuals ;, 2021)
This technical note and manual (TNM) addresses the following questions: (1) What are the main challenges in administering the value-added tax on imported digital services and the measures that countries have introduced to address the challenges?; (2) What are the main challenges in administering the value-added tax on low-value imported goods and the measures that countries have introduced to address the challenges? ;and (3) What are the key tasks in implementing the measures for improving the administration of the value-added tax on imported digital services and low-value imported goods?